2010
DOI: 10.1038/mp.2010.98
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of brain-derived neurotrophic factor in major depressive disorder: state–trait issues, clinical features and pharmacological treatment

Abstract: Recent evidence supports ‘the neurotrophin hypothesis of depression' in its prediction that brain-derived neurotrophic factor (BDNF) is involved in depression. However, some key questions remain unanswered, including whether abnormalities in BDNF persist beyond the clinical state of depression, whether BDNF levels are related to the clinical features of depression and whether distinct antidepressants affect BDNF levels equally. We addressed these questions and investigated serum BDNF levels in 962 depressed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
271
9
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(317 citation statements)
references
References 50 publications
31
271
9
6
Order By: Relevance
“…In line with a recent meta-analysis [ 14 ] , an epidemiological study (n = 962) found serum BDNF to be low in currently depressed subjects and to be normalized in remission, while antidepressants were diff erentially related to serum BDNF (St. John's wort > SSRI > venlafaxine > TCA > mirtazapine) [ 15 ] . Thus, antidepressants may diff er in their ability to induce BDNF.…”
Section: Changes Of Serum Concentrations Of Brain-derived Neurotrophimentioning
confidence: 68%
See 1 more Smart Citation
“…In line with a recent meta-analysis [ 14 ] , an epidemiological study (n = 962) found serum BDNF to be low in currently depressed subjects and to be normalized in remission, while antidepressants were diff erentially related to serum BDNF (St. John's wort > SSRI > venlafaxine > TCA > mirtazapine) [ 15 ] . Thus, antidepressants may diff er in their ability to induce BDNF.…”
Section: Changes Of Serum Concentrations Of Brain-derived Neurotrophimentioning
confidence: 68%
“…While there is evidence that diff erent classes of antidepressants differentially infl uence hypothalamus-pituitary-adrenal (HPA) axis parameters in humans [ 31 , 32 ] , there is only limited information on changes in BDNF serum concentrations after administration of diff erent antidepressants. Both, cross-sectional epidemiological [ 15 ] as well as longitudinal studies support the hypothesis that antidepressants have heterogeneous eff ects on serum BDNF [ 16 , 17 , 23 ] . Only few studies considered response to treatment to play a role in antidepressants' eff ects on serum BDNF.…”
Section: Bdnf [Ng/ml]mentioning
confidence: 90%
“…In turn, chronic administration of sertraline increases hippocampal BDNF mRNA levels in rats [9]. Similarly, SSRI-induced increases in serum BDNF levels have been detected in depressed patients [32]. Furthermore, SERT heterozygous null mice subjected to poor maternal care show elevated hippocampal BDNF mRNA levels relative to wild type controls undergoing identical experimental procedures [33].…”
Section: Discussionmentioning
confidence: 94%
“…1 The neurotrophin hypothesis of depression postulates that stress and depression are associated with decreased BDNF expression that can be reversed by antidepressant treatment. 2 The goal of the present study was to investigate the effect of antidepressant treatment on the epigenetic regulation of BDNF in major depressive disorder (MDD).The BDNF gene has distinct splice variants, each one regulated by a specific promoter region, that determine tissue-specific regulation of expression. 3 Of these variants, BDNF-IV is the most commonly studied and its expression changes have been associated with behavioural phenotypes, psychiatric disorders and epigenetic modifications.…”
mentioning
confidence: 99%
“…1 The neurotrophin hypothesis of depression postulates that stress and depression are associated with decreased BDNF expression that can be reversed by antidepressant treatment. 2 The goal of the present study was to investigate the effect of antidepressant treatment on the epigenetic regulation of BDNF in major depressive disorder (MDD).…”
mentioning
confidence: 99%